Formulasi Regulasi dan Kebijakan Komunikasi dalam Pelaksanaan Program Pembangunan: Studi pada Program Makan Bergizi Gratis - Amril, Amril; Sazali, Hasan (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
This study aims to analyze regulations and communication policies in the Free Nutritious Meal Program (MBG), focusing on the effectiveness of regulations as guidelines for regional implementers and communication barriers that interfere with implementation. Using a literature study and a descriptive qualitative approach, the data were analyzed thematically through relevant documents. The results show that the implementation of the program is still constrained by the absence of technical regulations, weak communication strategies, and low community participation. Other obstacles include the lack of operational guidelines, differences in understanding between implementers, digital divides, and low communication literacy. Therefore, this study recommends the need for a reformulation of communication policies that are inclusive, participatory, based on local culture, and supported by digital technology. This strategy is expected to strengthen the effectiveness of the implementation of the MBG program and encourage the creation of fair, equitable, and sustainable development in various regions of Indonesia.